The Relationship of Self-Regulation to Online-Fear of Missing Out (On-FoMO) in Famale Adolescent K-Pop Fans - masriani oktari; Utami, Rahayu Hardianti (Causalita, 2024)
K-Pop Teenage girls make K-Pop fans their identity. So that it raises curiosity about K-Pop and the desire to always be connected online. As a result, it raises anxiety or fear of missing out on valuable information and experiences about K-Pop (On-FoMO). This study aims to describe and test whether or not there is a relationship between self-regulation and Online-Fear of Missing Out (On-FoMO) in teenage girls who are K-Pop fans. The quantitative research method and using quota sampling and a sample size of 200 respondents with characteristics determined by the researcher. The research data were analyzed using the Pearson correlation test which showed a value of 0.109 and p = 0.124 (p> 0.05). The results of the study found that Ha was rejected and H0 was accepted, meaning that there was no relationship between self-regulation and Online-Fear of Missing Out (On-FoMO) in teenage girls who are K-Pop fans. The implications of the results of this study are that it provides a uniqueness that is different from previous studies, as a reference and shows that self-regulation is not the main predictor of On-FoMO in the context of female adolescent K-Pop fans, so that further researchers need to explore, study more deeply and look for other variables.